(untitled) (INNOTEC, 2022)
The aim of this work was to re-evaluate and find a use for human consumption of a by-product of the industrial brewing process, that contributes to the development of the circular economy. Grain powder is a by-product, obtained during the industrial brewing of beer and consists of a mixture of corn and barley, in an undefined proportion. Proximal characterization of the grain powder was performed followed by product development applying extrusion technology. Regarding the proximal characterization (humidity, proteins, ashes, fats and fiber), its high fiber content was highlighted. The development of products (snacks) was carried out taking into account the fiber content to obtain products with the claims “source of fiber” and “high in fiber” on their labeling according to the MERCOSUR regulation. A single screw extruder was used (constant speed of 150 rpm constant, temperature of 130 ℃) varying the humidity of the mixture, and the proportion of ingredients to achieve the highest consumer acceptability. The extruded snack with the highest acceptability was compared with two cereals from the market. It was possible to obtain a product ready-to-consume (product) using a by-product of the brewing process as a functional ingredient, with nutritional value, such as fiber content, beneficial for the prevention of non-communicable diseases.